The Importance of Emotional Intelligence in Education: Preparing an Emotionally Resilient Generation - Karolis Anaktototy; Samsudin Samsudin; Muhamad Sopyan; Tri Mulia Herawati; Meriyati Meriyati (Universitas Muhammadiyah Enrekang, 2024)
Education is an important foundation in shaping individuals to face the complex dynamics of life. However, the focus on academic achievement often ignores the emotional aspect. In this case, emotional intelligence (EQ) emerges as a key factor in preparing the younger generation to face life's challenges. This research explores the importance of emotional intelligence in education, with the aim of preparing an emotionally resilient generation. The research method used is a qualitative type with descriptive and comparative studies. This research collects data from various sources, including literature reviews and relevant documents. Qualitative and comparative analysis was carried out to understand the concept of emotional intelligence and its implementation in education.The research results show that the integration of emotional intelligence in the educational curriculum strengthens students' social skills and helps them cope better with stress. The role of parents and the school environment in supporting students' emotional development is also highlighted. Students with good emotional intelligence tend to achieve better academic results, emphasizing the positive impact of EQ development in education. Thus, this research provides insight into the importance of strengthening emotional aspects in learning. This not only improves academic performance, but also prepares students to face life's challenges with strong confidence and fortitude.